The Influence of Liquidity, Capital Structure and Dividend Policy on Return on Assets of FTSE ASEAN Stars Companies for the 2023–2024 Period - Novianti Dwi Pujiastuti; Dede Hertina (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the influence of liquidity, capital structure, and dividend policy on the Return on Assets (ROA) of companies listed in the FTSE ASEAN Stars Index during the 2023–2024 period. Liquidity is measured using the Current Ratio (CR), capital structure using the Debt to Equity Ratio (DER), and dividend policy using the Dividend Payout Ratio (DPR). This research employs a quantitative approach with multiple linear regression analysis. The sample consists of twenty-five companies selected through purposive sampling based on the completeness of financial statement data. The results indicate that the Current Ratio does not have a significant effect on Return on Assets, while the Debt to Equity Ratio has a negative and significant effect on Return on Assets. Dividend policy is also found to have no significant effect on Return on Assets. Simultaneously, the three independent variables significantly influence Return on Assets, with an explanatory power of 44.9%. These findings provide empirical insights into the financial factors affecting the profitability of ASEAN blue-chip companies and offer practical implications for management and investors in making financial decisions.